Late-in-life treadmill training rejuvenates autophagy, protein aggregate clearance, and function in mouse hearts - Cho, Jae Min; Park, Seul-Ki; Ghosh, Rajeshwary; Ly, Kellsey; Ramous, Caroline; Thompson, Lauren; Hansen, Michele; Mattera, Maria Sara de Lima Coutinho [UNESP]; Pires, Karla Maria; Ferhat, Maroua; Mookherjee, Sohom; Whitehead, Kevin J.; et al. (Wiley, 2021)
Protein quality control mechanisms decline during the process of cardiac aging. This enables the accumulation of protein aggregates and damaged organelles that contribute to age-associated cardiac dysfunction. Macroautophagy is the process by which post-mitotic cells such as cardiomyocytes clear defective proteins and organelles. We hypothesized that late-in-life exercise training improves autophagy, protein aggregate clearance, and function that is otherwise dysregulated in hearts from old vs. adult mice. As expected, 24-month-old male C57BL/6J mice (old) exhibited repressed autophagosome formation and protein aggregate accumulation in the heart, systolic and diastolic dysfunction, and reduced exercise capacity vs. 8-month-old (adult) mice (all p < 0.05). To investigate the influence of late-in-life exercise training, additional cohorts of 21-month-old mice did (old-ETR) or did not (old-SED) complete a 3-month progressive resistance treadmill running program. Body composition, exercise capacity, and soleus muscle citrate synthase activity improved in old-ETR vs. old-SED mice at 24 months (all p < 0.05). Importantly, protein expression of autophagy markers indicate trafficking of the autophagosome to the lysosome increased, protein aggregate clearance improved, and overall function was enhanced (all p < 0.05) in hearts from old-ETR vs. old-SED mice. These data provide the first evidence that a physiological intervention initiated late-in-life improves autophagic flux, protein aggregate clearance, and contractile performance in mouse hearts.
Keywords: aging; cardiac function; exercise; protein aggregates